Dicer1 dysfunction promotes stemness and aggression in endometrial carcinoma. Issue 4 (April 2017) - Wang, Xiao-Jun; Jiang, Fei-Zhou; Tong, Huan; Ke, Jie-Qi; Li, Yi-Ran; Zhang, Hui-Lin; Yan, Xiao-Fang; Wang, Fang-Yuan; Wan, Xiao-Ping
Endometrial carcinoma is one of the most common gynecological malignancies, but the molecular events involved in the development and progression of endometrial carcinoma remain unclear. Dicer1 and cancer stem cells play important roles in cell motility and survival. This study investigated the role of the let-7 family and Dicer1 in the stemness of endometrial carcinoma cells. We profiled Dicer1 expression in clinical samples and explored its relationship with stem cell–associated markers and clinical parameters. We showed that Dicer1 dysfunction leads to the enrichment of tumor stemness features and tumor aggression both in vitro and in vivo. We also identified the mechanism related to this potential tumor-predisposing phenotype: loss of Dicer1 induced abnormal expression of the let-7 family, which comprises well-known tumor suppressors, thus regulating stemness in endometrial carcinoma cells.